ChemInform Abstract: Access to Newly Functionalized Imidazole Derivatives: Efficient Synthesis of Novel 5‐Amino‐2‐thioimidazoles Using Propylphosphonic Anhydride (®T3P). Issue 25 (5th June 2015) - Lasalle, Manuel; Picon, Sylvain; Boulahjar, Rajaa; Hoguet, Vanessa; Van Obbergen, Jolien; Roussel, Pascal; Deprez, Benoit; Charton, Julie
Abstract: Various N‐acetamidoisothioureas undergo microwave assisted T3P‐mediated cyclodehydration to give imidazole derivatives.